Temporal-spatial changes and tourism efficiency coupling in Guangdong-Hong Kong-Macao Greater Bay Area - Kaijun Wu; Xilin Yang; Xingfu Han (PLoS ONE, 2025)
The Guangdong-Hong Kong-Macao Greater Bay Area (GBA) is an important tourist destination in China. However, the development of regional tourism is uneven, and there is an obvious center-periphery structure. It is significant to study the temporal and spatial evolution of the efficiency and scale of tourism economies and the relationship between them from the perspectives of economics and geography. The tourism scales of 11 cities in the GBA were calculated from 2001 to 2019. The Earth Science Data Acquisition (ESDA) method was used to investigate temporal-spatial differentiation characteristics and changes in tourism efficiency and scale. And it used a coupling coordination model to explore the superiority of coupling coordination and regional synergy. According to the findings, the GBA’s tourism efficiency rose steadily in fluctuations and then declined, whereas the tourism scale developed quickly, then slowly, followed by a steady upward trend. The efficiency and scale of tourism both have obvious spatial differences, and both the local spatial agglomeration effect and the spatial synergy of tourism become more and more significant. The coupling degree and coupling coordination degree between tourism efficiency and scale have evidently improved. Tourism efficiency and scale are currently primarily in the middle of mutual restraint and a low degree of mutual promotion.The importance of this paper stems primarily from its emphasis on temporal and spatial changes, as well as the coupling coordination of tourism efficiency and scale in GBA, as the majority of the existing literature focuses on temporal and spatial changes.